Predictors of work-related stress among nurses working in primary and secondary health care levels in Dammam, Eastern Saudi Arabia - Al-Makhaita, Huda M. (Medknow Publications & Media Pvt Ltd, 2014)
INTRODUCTION: Work-related stress (WRS) is an insidious and persistent part of everyday life related to the response of people to work environment. Nursing is a strenuous job and WRS is prevalent among nurses. The aim of this study was to estimate the prevalence of WRS among nurses working in primary and secondary health care levels in Dammam, Eastern Saudi Arabia. MATERIALS AND METHODS: A cross-sectional epidemiological study was conducted in 17 primary health care centers (PHCCs) representing the primary level of health care and  Medical Tower Complex (MTC) representing the secondary health care level in Dammam city. The total number of nurses included in the study was 637 nurses (144 in PHCCs) and (493 MTC). Data were collected using a self-administered questionnaire, which was developed based on the pertinent literature. It included two main parts: Sociodemographic and job characteristics of nurses and 31 WRS questions. RESULTS: The overall prevalence of WRS among all studied nurses was 45.5%; 43.1% and 46.2% in primary and secondary levels, respectively. In the primary level, there was a statistical significant association between WRS and being married (85.5%), and having living three children and more (53.2%). Moreover, younger age group 20-<30 years (79.4%), Saudi nationality (86.8%), being married (74.6%), having nonbachelor degree (83.3%), work shifts (89.5%), and working in surgical department (46.5%) were the significant associating factors with the occurrence of WRS among nurses in secondary levels. Young age was the only predicting factor for WRS in primary care level. While being female, Saudi, married, with work shifts, and working in surgical department were found to predict WRS in the secondary level. RECOMMENDATIONS: Appropriate strategy in health care organization to investigate stress in health care settings is recommended. Moreover, interventional programs to identify, and relieve sources and effects of stress should be developed.